Science at the frontier - Greenwood, Addison (National Academy Press, 1992)
Annotation At Frontiers of Science symposia, leading young scientists present and discuss their work with their peers in other fields, at a level intelligible across fields (e.g. a molecular biologist makes a presentation understandable to a geologist and vice versa). This book was a collaborative effort on the part of science writer Greenwood and 1990 symposium presenters to share the "frontiers" with a wider audience--scientists in various fields and serious lay readers; future volumes are planned for the 1991 and 1992 symposia. The following topics are addressed in separate chapters: geology, photosynthesis, dynamical systems, astrophysics, gene regulation, magnetic resonance imaging, computation, atmospheric science, neural networks, and physics. Each chapter contains a bibliography and a recommended reading list. Annotation c. by Book News, Inc., Portland, Or
Keywords: Discoveries in science.; Science.; Découvertes scientifiques.; Sciences.; sciences (philosophy); science (modern discipline); SCIENCE -- Essays.; SCIENCE -- Nanoscience.; SCIENCE -- Reference.; Discoveries in science; Science; Natuurwetenschappen.; Electronic books.; Overzichten (vorm)